Pioneers in Care: The Incorporation of Men in Nursing in Spain and Great Britain (1915-1980) - Jiménez Alcócer, Kevin Antonio (Investigación y Educación en Enfermería, 2025)
Objective. To describe the incorporation of the first male nurses in Spain and Great Britain between 1915 and 1980. Methods. This study adopted the analytical-synthetic historical method as epistemological framework to examine the evolution of the appearance of the first male nurses in Spain and Great Britain, supported by documentary sources from databases (SCIELO, SCOPUS, EBSCO, Google Scholar) using descriptors in Spanish, English, and Portuguese. Historical critique was applied at three levels: authenticity, representativeness, and relevance. The analysis combined temporal and thematic perspectives, examining causal factors, such as economic, social, ideological factors. Results. In Spain, nursing had segregated roles, women as nurses or midwives and men in the role of interns. In Great Britain, it was exclusively practiced by women. The Spanish Civil War and the dictatorship of Francisco Franco in Spain and the Second World War in Great Britain promoted male incorporation in both countries. The post-war periods and changes in gender roles facilitated a sociocultural transformation, integrating men into nursing and breaking stereotypes. This process redefined the profession, promoting equity and highlighting care beyond gender. Conclusion. The historical study reveals that nursing in Spain and Great Britain evolved from an exclusive profession for women toward a more inclusive model, defying stereotypes. Wars and social changes permitted incorporating men, redefining the professional identity. This transformation does not seek to privilege, rather, it seeks to highlight equity and that regardless of the sex or gender care can be provided as long as it has a scientific and ethical basis.